Voices in Transit - Salzer, Hanna; Hofmanner, Philip (Switzerland, 2006)
Timothy, Baddy and Osman are African asylum seekers in Switzerland. This film brings these three people out of anonimity and attempt by talking and listening to their stories to decipher their old-new idenities in a country that is not truly keen on welcoming aliens.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films